The Obama administration and educational reform - Zamani-Gallaher, Eboni M., 1971- (Bingley, U.K. : Emerald, 2014)
Arguably, since the day he was elected, President Barack Obama met great anticipation from scores of Americans regarding the forward course our nation desired economically, socially, and educationally. The promise of progress and social mobility that millions of U.S. families hope to attain can be unlocked through the educational enterprise. Unfortunately, while the United States educates all children, all children do not receive the same education. Hence, prospects for a better future for many are thwarted from the onset given the inequities in P-12 education. Furthermore, the pendulum is swinging as higher learning is becoming increasingly obstructed for many Americans across income brackets, gender, racial/ethnic backgrounds, abilities, and geographic areas.
Early childhood education in the context of educational reform : possibilities and causes for concern / Ruth Alfaro Piker, Abigail M. Jewkes -- Poverty and pretense : good intentions and misguided educational reform from No Child Left Behind through Race to the Top / Alison Dobrick -- Beyond the Common Core and the politics of education reform : the role of school counselors and teachers in facilitating the college and career readiness of urban students / Kalinda R. Jones ... [et al.] -- Bringing an end to the school to prison pipeline in the age of "post-racialism" / Marwin J. Spiller, Jeffrey Porter -- A perfect storm? President Obama, the great recession, and community colleges / Debra D. Bragg -- The 2020 American graduation initiative : a clear vision or dim view / J. Luke Wood, John D. Harrison -- Educational data crossroads : data literacy for data-driven decision making in postsecondary education / Soko S. Starobin, Sylvester Upah -- Regulating colleges and protecting students : gainful employment rules under the Obama administration / Ebony T. Jones -- Affirming acts for access and the evolving nature of affirmative action under the Obama administration / Denise O'Neil Green, Ghazala Knight, Matthew D. Green III -- Preparing the next generation of African American computing science faculty : a response to the Obama administration's scientific workforce priorities / LaVar J. Charleston, Jerlando F.L. Jackson, Juan E. Gilbert -- The handwriting on the wall for historically black colleges and universities : presence, policy, and praxis in Obamamerica / M. Christopher Brown II, Jarrett L. Carter, Sr., T. Elon Dancy II -- Obama's obstacles to educational change : race, racism, and reform / William A. Smith -- Undocumented students : the realities of immigration reform / Raul A. Leon -- Veteran education under the Obama administration / Shaftone B. Dunklin, Eboni M. Zamani-Gallaher -- Visibly invisible : federal educational policy regarding queer students, faculty, and staff during the Obama administration / Dafina-Lazarus Stewart, E.I. Annie Russell -- Access and equity for women in higher education during the era of the Obama administration : social identities, pay inequities, and the power of women's groups in changing leadership paradigms / Penny A. Pasque -- Healthy decisions and unintended consequences: implications of the protection and Affordable Care Act (ACA) for higher education / Robbya R. Green-Weir, Tamara N. Stevenson.
Print version record
Keywords: Education -- Educational Policy & Reform -- General; Education -- General; Educational strategies & policy; Educational change; Education and state -- United States; United States -- Politics and government -- 2009-